Computational intelligence based technique in multiple facts devices installation for power system security - Jumaat, S.A.; Musirin, I.; Othman, M.M.; Mokhlis, Hazlie (Journal of Theoretical and Applied Information Technology, 2012)
This paper presents a study on optimal location and sizing of multiple FACTS devices based on Particle Swarm Optimization (PSO) for minimization of transmission losses, and voltage profile improvement, which takes into account the cost of installation. In this study, Static Var Compensator (SVC) and Thyristor Controlled Series Compensator (TCSC) are chosen as the compensating device for the purposes of maintaining security in power system. Simulations for various loading conditions at several load buses have been conducted in order to evaluate its robustness and feasibility for broad implementation. In addition, installation of several FACTS devices into the system has been also conducted in the attempt to evaluate their impact to the system in terms of loss reduction and voltage profile improvement. Validation through the application on the IEEE 30-bus system indicated that PSO is feasible to achieve the task. Results from the study are compared with those obtained from Evolutionary Programming (EP) method in the attempt to highlight its merit.